Seasonal changes in epiphytic dinoflagellate assemblages near the northern coast of the Yucatan Peninsula, Gulf of Mexico - Okolodkov, Yuri B.; Merino Virgilio, Fany del Carmen; Aké Castillo, José Antolín; Aguilar Trujillo, Ana Concepción; Espinosa Matías, Silvia; Herrera Silveira, Jorge Alfredo (Instituto de Ecología, A.C., 2014)
Epiphytic dinoflagellates were studied in 250 samples from 10 sites in Chelem (a semi-enclosed mangrove lagoon) and Dzilam de Bravo (an exposed coastal locality), on the northern coast of the Yucatan Peninsula, during five surveys in 2008-2009. Temperature, salinity, turbidity, pH, dissolved oxygen, nitrates, nitrites, phosphates, silicates, urea, extractable water column chlorophyll-a, precipitation, and wind speed and direction were measured. The Chelem lagoon system showed minor variability in physical-chemical characteristics compared to the exposed site at Dzilam de Bravo. Dinoflagellates were associated with all the host macrophytes examined including four seagrass species and 33 macroalgal species representing 24 genera. A total of 20 dinoflagellate taxa from 12 genera were recovered from these substrates. The genus Prorocentrum contained the largest number of individual species. The variation in mean epiphytic dinoflagellate abundance over both localities ranged from ~200 to 3500 cells g-1substrate wet weight. Cell abundances at individual sites, in contrast, ranged from ~100 to >25 000 cells g-1 substrate wet weight. This variation is typical of the patchy distribution of these species in time and space. Overall, Prorocentrum rhathymum (up to 2.41x104 cells g-1) was the most abundant species observed across samples. Other abundant species were Bysmatrum caponii (maximum of 1.19x104cells g-1) and Amphidinium cf. carterae (maximum of 3.69x103 cells g-1). The highest abundances of Gambierdiscus species occurred in May and November (9.90x103 cells g-1) in Chelem when temperatures ranged from 24.5 to 30.2 oC. The data obtained indicate that the greatest potential for ciguatoxin flux into the food web may occur in protected, low turbulence environments, where salinities are high, nutrients abundant, and water temperatures are between 24 and 31 oC.